PENGARUH PEMBIAYAAN TERHADAP LABA BERSIH DENGAN FINTECH SEBAGAI VARIABEL MODERASI PERIODE 2015-2024 - Intan Rizkiana (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2026)
ABSTRACK This study aims to analyze the effect of Islamic financing (murabahah, mudharabah, musyarakah, ijarah, istishna, and qardh) on the net profit of Islamic banks, with fintech as a moderating variable, during the 2015–2024 period. The method used is multiple linear regression and moderation regression, utilizing SPSS version 27. The results show that, partially, only istishna financing has a significant effect on net profit. Murabahah, mudharabah, musyarakah, ijarah, and qardh do not have a significant effect. However, simultaneously, all financing variables significantly influence net profit. The moderation test reveals that fintech only moderates the effect of istishna financing on net profit, while it does not moderate the relationship for other types of financing. This may be due to the complexity of contracts, high risk, and the difficulty in automating management for certain financing schemes. Therefore, there is a need for fintech product innovations that are more aligned with the characteristics of Islamic financing, along with improved education and regulations. These findings are expected to serve as a reference for developing financing strategies and financial technology in the Islamic banking sector.